Foundations of Morality, Human Rights, and the Human Sciences
XVIII, 581 p.
Keywords: The essays in this volume constitute a portion of the research program being carried out by the International Society for Phenomenology and the Human Sciences. Established as an affiliate society of the World Institute for Ad vanced Phenomenological Research and Learning in 1976, in Arezzo, Italy, by the president of the Institute, Dr Anna-Teresa Tymieniecka, this particular society is devoted to an exploration of the relevance of phenomenological methods and insights for an understanding of the origins and goals of the specialised human sciences. The essays printed in the first part of the book were originally presented at the Second Congress of this society held at Purdue University, West Lafayette, Indiana, 12-14 July 1979. The second part of the volume consists of selected essays from the third convention (the Eleventh International Congress of Phenomenology of the World Phenomen ology Institute) held in Cambridge, Massachusetts in 1981. With the third part of this book we pass into the "Human Rights" issue as treated by the World Phenomenology Institute at the Interamerican Philosophy Congress held in Tallahassee, Florida, also in 1981. The volume opens with a mono graph by Anna-Teresa Tymieniecka on the foundations of ethics in the moral practice within the life-world and the social world shown as clearly distinct. The main ideas of this work had been presented by Tymieniecka as lead lectures to the three conferences giving them a tight research-project con sistency.